Structure of salts solution in polar dielectric liquids and electrically induced separation of solvated ions; Proceedings of SPIE; Vol. 9810 : Atomic and Molecular Pulsed Lasers XII - Shamanin I. V. Igor Vladimirovich (Laser Systems and New Laser and Optical Technologies, Laser Applications, 2015)
Title screen